2001
DOI: 10.1046/j.1471-4159.2001.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of NMDA receptor subunit expression and functional channel formation in the course of in vitro‐induced neurogenesis

Abstract: NE-7C2 neuroectodermal cells derived from forebrain vesicles of p53-de®cient mouse embryos (E9) produce neurons and astrocytes in vitro if induced by all-trans retinoic acid. The reproducible morphological stages of neurogenesis were correlated with the expression of various NMDA receptor subunits. RT-PCR studies revealed that GluR11 and GluR14 subunit mRNAs were transcribed by both non-induced and neuronally differentiated cells. GluR13 subunit mRNAs were not synthesized by NE-7C2 cells and increased numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Despite the fact that NR1 and some of the NR2 subunits were detected in the proliferative zones of the embryonic and perinatal brain [10,[104][105][106][107] or in dividing striatal progenitor cells in vitro [8], electrophysiological and Ca 2+ imaging experiments showed functional NMDA receptors only in young, postmitotic neurons just before or during the onset of their migratory processes [5,6,9,59,[108][109][110]. Similar delay between subunit expression and the formation of functional NMDA receptors was observed in ES cells and several neuronal progenitor cell lines during their in vitro neural differentiation [48][49][50][51][52][53][54][56][57][58]. These data suggest that proper intracellular trafficking and assembly of the subunits leading to the formation of functional heteromeric NMDA receptors requires a certain level of neuronal maturation, which is not achieved by dividing stem cells or neural precursors.…”
Section: Glu Receptors: Subunit Expression and Physiological Maturationmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the fact that NR1 and some of the NR2 subunits were detected in the proliferative zones of the embryonic and perinatal brain [10,[104][105][106][107] or in dividing striatal progenitor cells in vitro [8], electrophysiological and Ca 2+ imaging experiments showed functional NMDA receptors only in young, postmitotic neurons just before or during the onset of their migratory processes [5,6,9,59,[108][109][110]. Similar delay between subunit expression and the formation of functional NMDA receptors was observed in ES cells and several neuronal progenitor cell lines during their in vitro neural differentiation [48][49][50][51][52][53][54][56][57][58]. These data suggest that proper intracellular trafficking and assembly of the subunits leading to the formation of functional heteromeric NMDA receptors requires a certain level of neuronal maturation, which is not achieved by dividing stem cells or neural precursors.…”
Section: Glu Receptors: Subunit Expression and Physiological Maturationmentioning
confidence: 88%
“…By contrast, neuroectodermal stem cell lines have more limited ways of differentiation and generate only those cell types which are normally formed in the ventricular zone during development of the CNS. Using adequate protocols to induce neuronal differentiation in the cell lines, the role of Glu and their receptors during the proliferation, early development, neuronal maturation and lineage commitment has been investigated extensively [48][49][50][51][52][53][54][55][56][57][58]. Last, but not least, electrophysiological and/or histological observations in freshly isolated CNS tissue have also provided valuable experimental data on the direct and short-term effects of Glu on progenitor cell activity and metabolism [5,41,[59][60][61].…”
Section: Different Approaches To Study Neural Stem and Precursor Cellsmentioning
confidence: 99%
“…Previous studies showed that NMDARs are heteromeric composed of NR1 subunits, which binds glycine, and NR2 subunit, which binds glutamate; both NR1 and NR2 subunits are required to create a functional receptor (Waxman and Lynch 2005). Importantly, expression and function of the NMDAR protein appeared to be modulated in neural differentiation: (1) Neurogenesis is correlated with the expression of various NMDAR subunits (Varju et al 2001;Pizzi et al 2002), and (2) differentiation of the NG108-15 cells is associated with an increase in the NMDAR mRNA level (Beczkowska et al 1996(Beczkowska et al , 1997. Therefore, it is most likely that the selective vulnerability of the differentiated NG108-15 cells toward glutamate plus glycine, shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have noted NMDA receptors in proliferating neuroblasts from the ventral telencephalon germinal zones [Luk et al, 2003]. Interestingly, mRNA for the NR1 subunit of the NMDA receptor has been detected in multipotent forebrain precursors in vitro [Maric et al, 2000;Varju et al, 2001;Jelitai et al, 2002]. The observation that glutamate fails to influence proliferation and/or survival in early stem cell populations while influencing more differentiated neuroblasts could indicate that nonresponsive subpopulations lack functional receptor expression or downstream cellular pathways which couple receptor activation with proliferation [Maric et al, 2000].…”
Section: Mechanisms Underlying the Heterogeneous Response To Glutamatmentioning
confidence: 96%